High-Temperature and High-Pressure Phase Transition of Natural Barite Investigated by Raman Spectroscopy and Electrical Conductivity - Hong, Meiling; Dai, Lidong; Hu, Haiying; Zhang, Xinyu; Li, Chuang (Frontiers in Earth Science, 2022)
We investigated the structural, vibrational, and electrical transport properties for natural barite under the conditions of 298−873 K and 1.5−35.0 GPa using a diamond anvil cell by virtue of Raman spectroscopy and electrical conductivity measurements. Upon compression, natural barite transformed into post-barite at 18.9 GPa and atmospheric temperature, which was evidenced by the emergence of υ5 Raman peak, the discontinuities in the pressure-dependent Raman shifts, FWHM of υ1 Raman peak and electrical conductivity under non-hydrostatic condition. The phase transition is of good reversibility, whereas a considerable pressure hysteresis was detected during the process of decompression. Under quasi-hydrostatic condition, the structural transition of natural barite occurred at a higher pressure of 21.4 GPa, which is possibly related to the influence of deviatoric stress. Furthermore, our high-temperature and high-pressure Raman spectra and electrical conductivity results for natural barite revealed that the phase transformation pressures decreased as temperatures enhanced and further, the phase boundary between barite and post-barite was described as P (GPa) = 24.00 − 0.0166 T (K). Our obtained phase diagram of natural barite can improve the knowledge about the structural and electrical properties for other barite-group minerals MSO4 (M = Sr and Pb) under high temperature and high pressure conditions.